2012
DOI: 10.1016/j.ces.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetic modeling and analysis of ethanol partial oxidation and reforming reaction pathways on platinum at short contact times

Abstract: 2013iii ACKNOWLDGEMENTSThere are many people without whom this thesis would not have been possible. I must thank Ashish Mhadeshwar for the incredible amount of knowledge he imparted and the guidance he provided in order for this research to be conducted, shared at conferences and published. Many thanks to Doug Cooper, Bill Mustain and Ranjan Srivastava for standing in as advisors and providing support that was above and beyond expectations. I want to thank everyone that has become part of my UConn family, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Importantly, this first-principle analysis confirms the kinetic relevance of the H-abstraction steps that lead to acetaldehyde formation, postponing the C-C breaking stage, and the eventual re-equilibration of the fragments as precursors of CO, CO2, and methane ( Figure 9). A similarly comprehensive mechanism on platinum was developed by Koehle et al [69] for ethanol partial oxidation, where the total amount of reaction steps (50, each one considered in principle as reversible) was treated with a less aprioristic approach. The activation energy of every bond-break was estimated with a semi-empirical model, the so-called UBI-QEP, that relies on the interpolation of the calculated (or measured) binding energies of the intermediates with two parameters, catalyst coverage, and temperature, that are in turn eventually used to extrapolate the activation energies separating an intermediate from to the other.…”
Section: Calculated Energetic Profile Of Ethanol Degradationmentioning
confidence: 99%
“…Importantly, this first-principle analysis confirms the kinetic relevance of the H-abstraction steps that lead to acetaldehyde formation, postponing the C-C breaking stage, and the eventual re-equilibration of the fragments as precursors of CO, CO2, and methane ( Figure 9). A similarly comprehensive mechanism on platinum was developed by Koehle et al [69] for ethanol partial oxidation, where the total amount of reaction steps (50, each one considered in principle as reversible) was treated with a less aprioristic approach. The activation energy of every bond-break was estimated with a semi-empirical model, the so-called UBI-QEP, that relies on the interpolation of the calculated (or measured) binding energies of the intermediates with two parameters, catalyst coverage, and temperature, that are in turn eventually used to extrapolate the activation energies separating an intermediate from to the other.…”
Section: Calculated Energetic Profile Of Ethanol Degradationmentioning
confidence: 99%
“…The terms of A, Γ, T, To, β, E, and R represent for the pre-exponential factor, site density (1.5×10 15 sites/cm 2 or 2.49×10 −9 mol/cm 2 [28,29]), absolute temperature, reference temperature (300 K), temperature exponent, activation energy, and universal gas constant (8.314 J/mol•K), respectively. The fraction of vacant sites, θv, is given by:…”
Section: Ch4 Dry Reforming Processmentioning
confidence: 99%
“…It is evident that theoretical studies have focused on the decomposition pathways of ethanol, while all previously reported microkinetic models on ethanol conversion towards syngas are over noble metals, namely Pt [19,26] and Rh [27]. It is recognised though that the high cost of the latter poses significant economic difficulties to the commercial implementation of the process.…”
Section: Introductionmentioning
confidence: 99%